Prognostic and Clinicopathological Significance of PD-L1 in Patients With Bladder Cancer: A Meta-Analysis - Zhu, Lei; Sun, Jin; Wang, Ling; Li, Zhigang; Wang, Lei; Li, Zhibin (Frontiers in Pharmacology, 2019)
Background: The prognostic role of programmed cell death-ligand 1 (PD-L1) in bladder cancer has been investigated in previous studies, but the results remain inconclusive. Therefore, we carried out a meta-analysis to evaluate the prognostic significance of PD-L1 in patients with bladder cancer. Methods: The electronic databases PubMed, Embase, Web of Science, and Cochrane Library were searched. The association between PD-L1 expression and survival outcomes and clinicopathological factors were analyzed by hazard ratios (HR) or odds ratios (OR) and 95% confidence intervals (CI). Results: A total of 11 studies containing 1697 patients were included in the meta-analysis. High PD-L1 expression was associated with poor overall survival (OS) (HR=1.83, 95%CI=1.24-2.71, p=0.002). There was non-significant association between PD-L1 and recurrence-free survival (RFS) (HR= 1.43, 95%CI=0.89-2.29, p=0.134), cancer-specific survival (CSS) (HR=1.51, 95%CI=0.80-2.87, p=0.203), or disease-free survival (DFS) (HR=1.53, 95%CI=0.88-2.65, p=0.13).Furthermore, high PD-L1 was significantly correlated with higher tumor stage (OR=3.9, 95%CI=2.71-5.61, p<0.001) and distant metastasis (OR=2.5, 95%CI=1.22-5.1, p=0.012). While PD-L1 overexpression was not correlated with sex, tumor grade, lymph node status, and multifocality. Conclusions: The meta-analysis suggested that PD-L1 overexpression could predict worse survival outcomes in bladder cancer. High PD-L1 expression may act as a potential prognostic marker for patients with bladder cancer.